Acute upper respiratory tract infections in children: antibiotic therapy - D. A. Tulupov; E. P. Karpova (Медицинский совет, 2018)
This article provides an overview of the current clinical guidelines and consensus papers on the role of bacterial infection, indications and algorithm for antibiotic therapy in the treatment of the most common acute upper respiratory tract infections in children: acute rhinosinusitis, acute otitis media and acute tonsillitis.